2017
DOI: 10.1111/ahg.12234
|View full text |Cite
|
Sign up to set email alerts
|

Expression of miRNA‐146a, miRNA‐155, IL‐2, and TNF‐α in inflammatory response to Helicobacter pylori infection associated with cancer progression

Abstract: miRNAs appear to play an important role in controlling the expression of several genes, and they are a potential biomarker and prognostic tool in gastric diseases. We analyzed 53 controls, 86 patients with gastritis, and 19 patients with gastric cancer. Real-time-PCR was used to determine the expression levels of miRNA-146a, miRNA-155, IL-2, and TNF-α. The subsequent analysis of the target genes was performed using the bioinformatics approach. There was no difference in IL-2 expression between the groups. Howe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 34 publications
1
13
0
2
Order By: Relevance
“…MiRNAs have no ability to encode proteins, but contribute to the modulation of gene expression[11,12]. A recent study revealed the upregulation of miR-146a and miR-155 in patients with gastritis induced by H. pylori infection[13], with the similar findings demonstrated by another research group[14]. Cortés-Márquez et al[14] further grouped the patients with gastritis by age, and found that both children and adults with H. pylori -induced gastritis displayed higher levels of miR-145a and miR-155.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…MiRNAs have no ability to encode proteins, but contribute to the modulation of gene expression[11,12]. A recent study revealed the upregulation of miR-146a and miR-155 in patients with gastritis induced by H. pylori infection[13], with the similar findings demonstrated by another research group[14]. Cortés-Márquez et al[14] further grouped the patients with gastritis by age, and found that both children and adults with H. pylori -induced gastritis displayed higher levels of miR-145a and miR-155.…”
Section: Introductionmentioning
confidence: 99%
“…Cortés-Márquez et al[14] further grouped the patients with gastritis by age, and found that both children and adults with H. pylori -induced gastritis displayed higher levels of miR-145a and miR-155. Moreover, the cancerization tendency of H. pylori -induced gastritis was correlated with the upregulation of miR-146a and miR-155[13,14]. In addition, H. pylori infection could result in the downregulation of miRNAs.…”
Section: Introductionmentioning
confidence: 99%
“…The relative expression levels of TLR9 mRNA were measured by real-time quantitative PCR based on the TaqMan ® System (Life Technologies, Carlsbad, CA, United States) within the StepOne Plus Real-Time PCR system 2.2.3 (Applied Biosystems) using a specific TaqMan probe for TLR9 (H00002973_m1) and two reference genes, GUSB (Hs00187320_m1) and TBP (Hs00187332_m1) which were tested in a previous study[19]. A pool of normal H. pylori- negative gastric tissue samples was used as a calibrator.…”
Section: Methodsmentioning
confidence: 99%
“…O aumento da expressão do RNAm de TNF- em pacientes com neoplasia gástrica foi associado à presença do vírus H. pilory (Zabaglia et al, 2017;Hosseinzadeh et al, 2016 (Liu et al, 2008). Não houve diferença na expressão de RNAm de TNF-α em tecido neoplásico gástrico antes e após 3 semanas do emprego do quimioterápico cisplatina (Hosseinzadeh et al, 2016), assim como entre indivíduos que receberam ou não quimioterapia neoadjuvante para câncer gastroesofágico (Deans et al, 2006).…”
Section: Marcadores Inflamatóriosunclassified
“…Uma limitação do presente estudo se refere ao pequeno tamanho amostral, especialmente se comparado com estudos japoneses ou multicêntricos (Kim et al, 2017;Su et al, 2014;Liang et al, 2011). Entretanto, o número de casos avaliados foi igual ou superior (Augusto et al, 2007;Zabaglia et al, 2017) a outros estudos que analisaram a expressão do RNAm de citocinas inflamatórias. Na literatura, muitos estudos incluem pacientes com tumores variados do trato digestório (Matos-Neto et al, 2015;Shibata et al, 2008;Deans et al, 2006…”
Section: Forças E Limitações Do Estudounclassified